Assessing Customer Needs Using a Hybrid Technique Including QFD and DEMATEL in Fuzzy Conditions (Case Study: Service Company RAZI Industrial Town: Industrial Town Corporation Isfahan Province) - Seyed Mohammad Reza Davoodi; Mohammad Ebrahim Khatami (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: In today's world, due to the increasing progress of the world in various fields, the needs and wants of customers in improving the quality of services and consumer goods have increased. These needs, which occur implicitly and explicitly, have grown significantly in all areas of industrial units. On the other hand, organizations that seek to meet customer expectations and needs are forced to use the tools and systems that they have. Quality performance enhancement is one of the most essential tools to help achieve this goal.Methodology: This study intends to evaluate the needs of companies using a questionnaire and a combination of quality performance and fuzzy DEMATEL. The statistical population of this research includes service companies in Razi industrial town. Using Cochran's formula, 120 companies were selected as a sample, and a needs prioritization questionnaire was sent to them.Findings: Based on the research results, the company identified 64 needs, and drinking water was the company's priority. Then, this company identified 8 services or technical requirements, and the Quality House determined the relations between the needs of Razi Industrial City Service Company customers. Service priority was set.Originality/Value: The quality performance enhancement technique is an essential tool for translating the customer's voice, considering their wants and needs, and prioritizing the technical requirements of production, which was used for the first time in this study.